2018
DOI: 10.1002/2017rg000567
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Extreme Atmospheric Hazards and Global Teleconnections: Implications for Multihazard Resilience

Abstract: Occurrences of concurrent extreme atmospheric hazards represent a significant area of uncertainty for organizations involved in disaster mitigation and risk management. Understanding risks posed by natural disasters and their relationship with global climate drivers is crucial in preparing for extreme events. In this review we quantify the strength of the physical mechanisms linking hazards and atmosphere‐ocean processes. We demonstrate how research from the science community may be used to support disaster ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 232 publications
(337 reference statements)
2
43
0
Order By: Relevance
“…The time series of the smoothed Nino3.4 index in Figure shows that the major droughts are closely related to prolonged La Niña events. Many studies have echoed the significant contribution of the tropical Pacific Ocean to major droughts in the CONUS (e.g., Cole et al, ; Cook et al, ; Hu & Huang, ; Okumura et al, ; Steptoe et al, ). From their millennial assessment, for example, Cook et al () suggested that a long‐lasting extensive drought in the CONUS is a part of the climatic response to persistent La Niña‐like conditions in the tropical Pacific Ocean.…”
Section: Resultsmentioning
confidence: 99%
“…The time series of the smoothed Nino3.4 index in Figure shows that the major droughts are closely related to prolonged La Niña events. Many studies have echoed the significant contribution of the tropical Pacific Ocean to major droughts in the CONUS (e.g., Cole et al, ; Cook et al, ; Hu & Huang, ; Okumura et al, ; Steptoe et al, ). From their millennial assessment, for example, Cook et al () suggested that a long‐lasting extensive drought in the CONUS is a part of the climatic response to persistent La Niña‐like conditions in the tropical Pacific Ocean.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged weather extremes result dynamically from long‐lived atmospheric flow patterns, whose duration spans from days to weeks (Higgins and Mo, ; Stadtherr et al., ; Mann et al., ; Kornhuber et al., ). Recurrent atmospheric teleconnections composed of adjacent cyclones/anticyclones are deemed one major source for the persistence of weather extremes (Chen and Zhai, ; Lü et al ., ; Steptoe et al., ). Monthly‐/seasonal‐scale indices of atmospheric teleconnections used to be employed in explaining, monitoring and predicting climate anomalies at interannual to inter‐decadal time‐scales (Wallace and Gutzler, ; Nitta and Hu, ; Kubota et al., ).…”
Section: Introductionmentioning
confidence: 97%
“…For PC2 also, the SSTa cluster over the tropical western Pacific and eastern Indian Oceans, around the Maritime continents and adjacent to northern Australia was significant. Existing literature indicated that the tropical Pacific's ENSO is a primary driver of global climate variability [18][19][20] , influencing several croplands across the world 10,21,22 ; but using different approach and datasets our analysis confirms that the tropical Pacific SST can explain two leading modes of world-wide wheat yield variability and beyond. This finding was further substantiated by another set of findings shown in Table S3 indicating that ENSO indices, peaking mostly in winter (December-January-February), associate best with PC1 variability, and to an opposite manner with PC2.…”
Section: Resultsmentioning
(Expert classified)